The Urgency of Effective Archive Management in Supporting Smooth Administration and Organizational Decision-Making - Aria Mulyapradana; Aghus Jamaludin Kharis; Munisa Nur; M. Agustino N; M. Saefullah (International Journal of Economics and Management Research, 2026)
This study aims to analyze the urgency of effective archival management in supporting smooth administration and decision-making within organizations. In the digital transformation era, archives are no longer just static documents, but strategic assets that ensure accountability and efficiency. A qualitative descriptive research method was used, employing data collection techniques such as in-depth interviews, field observations, and documentation studies. Data analysis involved data reduction, presentation, and drawing conclusions. The study found that systematic archive management significantly improves administrative processes by reducing document retrieval time to under two minutes. Additionally, archives serve as vital tools in evidence-based policymaking, where leaders use authentic records to minimize risks and ensure the legality of decisions. However, the study also identified challenges, including limited human resource competencies and incomplete digital infrastructure integration. The study concludes that effective archive management is a critical pillar for good organizational governance. It is recommended that organizations enhance archival human resource capacity and invest in electronic archive systems to ensure operational continuity and support accurate decision-making in the future.